SYSTEM OF INTERNAL GOVERNMENT AUDIT IN THE REPUBLIC OF KAZAKHSTAN - Igibaeva Z.K, (Academic Journal of Physical and Chemical Sciences, 2019)
The study presents the system of internal state audit of the Republic of Kazakhstan, discusses the problematic aspects of their implementation and the prospects for their resolution in the reform process. The system of financial control of Kazakhstan is undergoing a stage of radical reform. The transformation of the internal public audit system requires the reform of all elements of the existing control system. The creation of effective mechanisms for implementing the principles lays the foundation for the effective functioning of the state audit system in the financial management of state bodies. In order to create an effective state audit system, measures have been identified for its implementation, in particular, to improve the quality of control measures and ensure their compliance with international standards.